(untitled) (World of finance, 2019)
Introduction. Assessment of the probability of insurance companies insolvency in modem conditions will determine not only the real state of doing business, but also identify critical moments in the activities ofinsurers. Purpose. The purpose of the article is to assess the probability of bankruptcy of a functioning insurance company on the basis ofmodels used in world practice. Results. The authors argue that the assessment of the probability of insurance companies insolvency in modern economic conditions will determine not only the real state of doing business, but also identify critical moments in the activities ofinsurers. The basis of the analysis of the insurer’s predisposition to bankruptcy is discriminant bankruptcy probability models used by both ordinary enterprises and insurers. Based on the one-factor discriminant analysis, a model is developed which enables us to assess the general state of the insurer according to individual criteria-indicators, without using weight of coefficients and values of indicators.. An overview of the methods forassessing the probability of bankruptcy and their comparative characteristics is reviewed, the factors of problems ofthe use offoreign discriminatorymodels in Ukraine are determined. Conclusion. A critical assessment ofthe prevailing in foreign practice and the theory methodological approaches to the analysis of the bankruptcy probability allows us to conclude that some models are contradictory because, with the simultaneous use of them, it is possible to obtain conclusions opposite to each otherregarding the bankruptcyprobabilityofa particularentity. Despite some disadvantages, these models have high probability of evaluation and are very effective in practice. Discriminant models can be used to confirm the results both separately and in aggregate, however, with a certain correction. The most significant relationship between models in dynamics, because one-time analysis may not give correct results. All models contain a set ofdiffer-entindicators thathave territorial specificity, and none ofthem can claim to be universal.